Water cluster fragmentation probed by pickup experiments - Huang, Chuanfu; Kresin, Vitaly V; Pysanenko, Andriy; Fárník, Michal (The Journal of chemical physics, 2016)
Electron ionization is a common tool for the mass spectrometry of atomic and molecular clusters. Any cluster can be ionized efficiently by sufficiently energetic electrons, but concomitant fragmentation can seriously obstruct the goal of size-resolved detection. We present a new general method to assess the original neutral population of the cluster beam. Clusters undergo a sticking collision with a molecule from a crossed beam, and the velocities of neat and doped cluster ion peaks are measured and compared. By making use of longitudinal momentum conservation, one can reconstruct the sizes of the neutral precursors. Here this method is applied to H2O and D2O clusters in the detected ion size range of 3-10. It is found that water clusters do fragment significantly upon electron impact: the deduced neutral precursor size is ∼3-5 times larger than the observed cluster ions. This conclusion agrees with beam size characterization by another experimental technique: photoionization after Na-doping. Abundant post-ionization fragmentation of water clusters must therefore be an important factor in the interpretation of experimental data; interestingly, there is at present no detailed microscopic understanding of the underlying fragmentation dynamics.